Ribosomal protein S3 regulates GLI2-mediated osteosarcoma invasion. Issue 2 (28th January 2015) - Nagao-Kitamoto, Hiroko; Setoguchi, Takao; Kitamoto, Sho; Nakamura, Shunsuke; Tsuru, Arisa; Nagata, Masahito; Nagano, Satoshi; Ishidou, Yasuhiro; Yokouchi, Masahiro; Kitajima, Shinichi; Yoshioka, Takako; Maeda, Shingo; et al.
Highlights: RPS3 was identified as a novel downstream gene of GLI2. Knockdown of GLI2 decreased RPS3 expression in osteosarcoma cells. RPS3 knockdown decreased the migration and invasion of osteosarcoma cells. RPS3 expression was increased in primary osteosarcoma lesions with lung metastases. GLI2–RPS3 pathway may be an attractive therapeutic target for treating osteosarcoma metastasis. Abstract: It has been reported that GLI2 promotes proliferation, migration, and invasion of mesenchymal stem cell and osteosarcoma cells. To examine the molecular mechanisms of GLI2-mediated osteosarcoma metastasis, we performed a microarray analysis. The gene encoding ribosomal protein S3 ( RPS3 ) was identified as a target of GLI2. Real-time PCR revealed that RPS3 was upregulated in osteosarcoma cell lines compared with normal osteoblast cells. Knockdown of GLI2 decreased RPS3 expression, whereas forced expression of a constitutively active form of GLI2 upregulated the expression of RPS3. RPS3 knockdown by siRNA decreased the migration and invasion of osteosarcoma cells. Although forced expression of constitutively active GLI2 increased the migration of human mesenchymal stem cells, knockdown of RPS3 reduced the up-regulated migration. In contrast, forced expression of RPS3 increased migration and invasion of osteosarcoma cells. Moreover, reduction of migration by GLI2 knockdown was rescued by forced expression of RPS3 . Immunohistochemical analysis showed that RPS3 expression was increased in primary osteosarcoma lesions with lung metastases compared with those without. These findings indicate that GLI2–RPS3 signaling may be a marker of invasive osteosarcoma and a therapeutic target for patients with osteosarcoma.